Eksegese is 'n spel (sonder reëls?) - W. S. Prinsloo (Acta Theologica)
In his article "Eksegese is 'n spel" (Exegesis is a game), JH le Roux draws a caricature of the text immanent approach, is guilty of generalizations and employs an obsolete idea of the text immanent approach. With this misrepresentation he comes into conflict with the Gadamer approach - the approach which he himself advocates. He therefore violates the rules of the game which he has devised.